2015
DOI: 10.1007/s13594-015-0212-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray analysis of the antihypertensive effect of milk fermented by Lactobacillus helveticus H9 on spontaneously hypertensive rats

Abstract: Although an antihypertensive effect of fermented milk has been demonstrated in many human and animal experiments, the molecular mechanism controlling it is still poorly understood. In this study, we used DNA microarray analysis to determine the molecular mechanism of the antihypertensive effect of fermented milk. The results showed that gene expression in the left ventricle of spontaneously hypertensive rats was regulated when milk fermented by Lactobacillus helveticus (L. helveticus) H9 was administered. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Recently, the same technology was used to determine the molecular mechanism of the antihypertensive effect of milk fermented by Lactobacillus helveticus. 118 It was found that hypertensionassociated genes differentially expressed in the left ventricle of SHR were related to NO synthesis, cell proliferation, ET binding and blood clot breakdown. Specifically, regulation of eNOS, PPARγ and ET A receptor genes could be responsible for the antihypertensive response provoked by fermented milk treatment.…”
Section: Effects On the Endothelin Systemmentioning
confidence: 99%
“…Recently, the same technology was used to determine the molecular mechanism of the antihypertensive effect of milk fermented by Lactobacillus helveticus. 118 It was found that hypertensionassociated genes differentially expressed in the left ventricle of SHR were related to NO synthesis, cell proliferation, ET binding and blood clot breakdown. Specifically, regulation of eNOS, PPARγ and ET A receptor genes could be responsible for the antihypertensive response provoked by fermented milk treatment.…”
Section: Effects On the Endothelin Systemmentioning
confidence: 99%
“…However, the sophisticated fermentation process, in which numerous reactions take place simultaneously, has generally only been characterised by determining a small number of compounds. In addition, the mechanism producing bioactive peptides has been demonstrated through the characterisation of gene expression in the proteolytic system (Zhang et al ., ; Chen et al ., ,c).…”
Section: Introductionmentioning
confidence: 99%